Gendered expectations and the framing of Afghan women in peacebuilding: a critical discourse analysis - Fornaciari, Federica; Goldman, Laine (Critical discourse studies, 2025)
Despite the invaluable role that women play in the peacebuilding process, statistics still show this as a male-dominated field. Since media narratives have the power to frame reality providing the public with preferred lenses to understand it, this study asks, How do media narratives frame the role of Afghan women in conflict resolution? To address this question, we combine Frame Theory (Entman, R. M. (1993). Framing: Toward clarification of a fractured paradigm. Journal of Communication, 43(4), 51-58) and Critical Discourse Analysis (van Dijk, T. A. (2015). Critical discourse analysis. In D. Tannen, H. E. Hamilton, & D. Schiffrin (Eds.), The handbook of discourse analysis (pp. 466-485). Wiley Blackwell) to explore media narratives before and after the Taliban came into power in August 2021. The samples include 32 articles published between 2018 and 2022 on different sources ranging from traditional news outlets to magazines, newsrooms, intergovernmental organizations, and think tanks. Findings show that media narratives perpetuate unfair gendered expectations, failing to effectively render the irreplaceable role of women in peacebuilding. Frames confirm the double bind of hegemonic femininity (Schneiker, A. (2021). The UN and women's marginalization in peace negotiations. International Affairs, 97(4), 1165-1182) as women are subject to different expectations - the exception presents them as courageous, yet the norm frames them as being too vulnerable and without a voice.